Study of the Tourism Market in Serang Regency Post COVID-19 Pandemic - Rifki Rahmanda Putra; Ajeng Ramadhita Larasati; Irwan Tamrin (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2024)
The objective of this study was to examine the domestic tourism market in Serang Regency, focusing on the characteristics, behavior, and typology of tourists that visited the region over the period of 2021-2022. This endeavor is undertaken by the Serang Regency Government to discern the prevailing tourism patterns following the pandemic. Approach This study utilized a descriptive research method with a quantitative approach to accomplish its objectives. A survey was conducted on a sample of 203 respondents using the basic random sampling approach. Most tourists visiting Serang Regency can be classified as dedicated nature tourists. They are motivated to visit coastal locations for social interaction, whereas their motive is to travel to the highlands in Serang Regency for the purpose of seeking novelty and acquiring new knowledge. Tourists tend to prioritize activities that provide relaxation in natural environments. The findings of this research on the tourism market in Serang Regency have significant significance. They can serve as a valuable resource for formulating effective tourism marketing policies and enhancing the development of tourism products in Serang Regency. To evaluate the efficacy of implementing the findings of this study, it is imperative to conduct additional scientific research, such as an examination of the elements that impact tourists' pleasure and decision-making to visit Serang Regency.